The japanese economy - Allen, George Cyril (St. Martin's Press, 1981)
In The Japanese Economy, G. C. Allen draws on his more than sixty years of study and firsthand dialogues with Japanese economists, civill servants, and businessmen, to produce this outstanding look at what makes Japan's economy fick...